Information asymmetries and identification bias in P2P social microlending. Issue 1 (2nd January 2017) - Riggins, Frederick J.; Weber, David M.
ABSTRACT: The Internet has created new opportunities for peer-to-peer (P2P) social lending platforms, which have the potential to transform the way microfinance institutions raise and allocate funds used for poverty reduction. Depending upon where decision-making rights are allocated, there is the potential for identification bias whereby lenders may be motivated to give to specific projects with which they have an affinity without regard to whether it represents a sound financial investment. Using data collected from Kiva, we present empirical evidence that distant upstream lenders do not have adequate information about local business and loan conditions to make sound microfinance funding decisions, but instead make decisions based on identification biases. Furthermore, more information provided on the P2P lending site about the prospective loan does not improve the lender's information about the loan conditions, but rather exacerbates the identification bias effect.